2017
DOI: 10.11648/j.ajam.20170505.11
|View full text |Cite
|
Sign up to set email alerts
|

MHD Convection Fluid Flow and Heat Transfer in an Inclined Microchannel with Heat Generation

Abstract: Abstract:The problem of fully developed free convection flow of electrically conducting fluid in an inclined microchannel in the presence of transverse magnetic field and internal heat generation is investigated. The analytical solution for velocity profile and temperature profile have been obtained, considering the velocity slip and temperature jump conditions at the wall of the microchannel. The effect of different parameters involved in the problem on the velocity and temperature profile along with the skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Jha et al [28] evaluated the natural convective viscous fluid flow past in an upright parallel plate channel. The significant existence of a magnetic force in a free convective, electrically conducting liquid flowing in an oblique channel was deliberated by Zaidi and Ahmad [29] and also discussed the outturn of different parameters including Nusselt number and skin friction. Monaledi and Makinde [30] used the Buongiorno model to study entropy in a Poiseuille flow of nanoliquid through a microchannel with injection and distribution and the outcome showed that skin friction was reduced by the accumulation of nanoparticles towards the center of the channel.…”
Section: Introductionmentioning
confidence: 99%
“…Jha et al [28] evaluated the natural convective viscous fluid flow past in an upright parallel plate channel. The significant existence of a magnetic force in a free convective, electrically conducting liquid flowing in an oblique channel was deliberated by Zaidi and Ahmad [29] and also discussed the outturn of different parameters including Nusselt number and skin friction. Monaledi and Makinde [30] used the Buongiorno model to study entropy in a Poiseuille flow of nanoliquid through a microchannel with injection and distribution and the outcome showed that skin friction was reduced by the accumulation of nanoparticles towards the center of the channel.…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al [17] utilized Galerkin weighted residual finite-element technique to analyze problems of heat transfer flow of nanofluid in the presence of natural convection. Zaidi and Ahmad [18] studied the effects of heat generation on buoyancy driven flow of viscous fluid through an inclined microchannel with slip conditions. Adegbie et al [19] analytically examined the impacts of pertinent fluid parameters on free convective flow of Newtonian fluid past a continuous moving surface.…”
Section: Introductionmentioning
confidence: 99%